The influence of Methylphenidate on the development of the forensically significant blow fly Chrysomya chloropyga (Diptera: Calliphoridae) in the Western Cape Province - Visser, Hartwig (Division of Forensic Medicine and Toxicology, 2016)
Forensic entomologists rely on insect development and successional data to estimate the post-mortem interval (PMI). Ante-mortem drug use prior to an individual's death may result in drug transmission to feeding insects and subsequent alteration of their development, thereby altering PMI estimates. This study investigated the influence of Ritalin (methylphenidate hydrochloride) (MPH) on the development of Chrysomya chloropyga. C. chloropyga larvae were reared on pig liver treated with MPH and exhibited a trend of expedited larval development and prolonged pupal development. Conservatively, the results suggest that MPH may expedite the larval stage by up to 17 hours and prolong the pupal stage by up to 16 hours. These preliminary findings suggest that, at the concentration investigated, MPH may alter the duration of C. chloropyga developmental stages, and consequently PMI estimates if MPH is not detected or its effects not considered. Furthermore, MPH was detected in both frozen and ethanol preserved specimens. MPH could still be detected from treated larvae, after 3.5 days incubation at ~30°C. This may suggest an improved stability of MPH in insects. Moreover, detection of MPH from ethanol preserved specimens suggests the qualitative toxicological utility of specimens maintained in this preservation liquid, despite stability and self-extraction concerns. These are the first entomotoxicological data on MPH generated for blow flies local to the Western Cape, South Africa.